HISTOPATOLOGY OF Mystus nemurus OF LIVER THAT IMMERSED WITH Curcuma xanthorrhiza ROXB Extract AND WERE INFECTED BY Edwardseilla tarda - Rubianto '; Morina Riauwaty; Iesje Lukistyowati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This study was conducted over three months in the laboratory of Fish Diseases and Parasites, Faculty of Fisheries and Marine Sciences University of Riau Pekanbaru. The purpose of this research was to determine the structure of (Mystus nemurus) liver that were immersed with Curcuma xanthorrhiza ROXB extract and were infected by Edwardseilla tarda and to find out best dose Curcuma xanthorrhiza ROXB extract for the prevention of Edwardsiella tarda infections. The method used is an experimental method at a dose of treatment and analyzed descriptive. The treatment used is an extract of Curcuma xanthorrhiza ROXB with different concentrations, they were: Kn (Fishes were not receive any treantent), Kp (Fishes were not receive any treatment but were infected with E. tarda), P1 (immersed in curcuma with concentration 0,2 g/l), P2 (immersed in curcuma with concentration 0,4 g/l), P3 (immersed in curcuma with concentration 0,6 g/l) and were infected with E. tarda (0.1 ml of 108 of E. tarda), Fish organ (liver) were processed for histological studied (formalin fixed, alcohol series, 6 sliced and HE Stained). Result indicate that the structure of liver of the treated fish showing abnormality symptoms, such as necrosis, congestion, fatted degeneration and hemorrhage. From these, it can be concluded that immirsion in Curcuma with 0.6 g / l concentration is capable of inhibiting bacterial Edwardsiella tarda.Key word : Liver, Mystus nemurus, Curcuma xanthorrhiza ROXB, Edwardsiella tarda